Long-acting injectable paliperidone palmitate versus oral paliperidone extended release: a comparative analysis from two placebo-controlled relapse prevention studies - Markowitz, Michael (BioMed Central, 2013)
BACKGROUND: Increasing availability and use of long-acting injectable antipsychotics have generated a need to compare these formulations with their oral equivalents; however, a paucity of relevant data is available. METHODS: This post hoc comparison of the long-term efficacy, safety and tolerability of maintenance treatment with paliperidone palmitate (PP) versus oral paliperidone extended release (ER) used data from two similarly designed, randomised, double-blind (DB), placebo-controlled schizophrenia relapse prevention trials. Assessments included measures of time to relapse, symptom changes/functioning and treatment-emergent adverse events (TEAEs). Time to relapse between treatment groups was evaluated using a Cox proportional hazards model. Between-group differences for continuous variables for change scores during the DB phase were assessed using analysis of co-variance models. Categorical variables were evaluated using Chi-square and Fisher's exact tests. No adjustment was made for multiplicity. RESULTS: Approximately 45% of enrolled subjects in both trials were stabilised and randomised to the DB relapse prevention phase. Risk of relapse was higher in subjects treated with paliperidone ER than in those treated with PP [paliperidone ER/PP hazard ratio (HR), 2.52; 95% confidence interval (CI), 1.46–4.35; p < 0.001]. Similarly, risk of relapse after withdrawal of paliperidone ER treatment (placebo group of the paliperidone ER study) was higher than after withdrawal of PP (paliperidone ER placebo/PP placebo HR, 2.25; 95% CI, 1.59–3.18; p < 0.001). Stabilised schizophrenic subjects treated with PP maintained functioning demonstrated by the same proportions of subjects with mild to no difficulties in functioning at DB baseline and end point [Personal and Social Performance (PSP) scale total score >70, both approximately 58.5%; p = 1.000] compared with a 10.9% decrease for paliperidone ER (58.5% vs 47.6%, respectively; p = 0.048). The least squares mean change for Positive and Negative Syndrome Scale (PANSS) total score at DB end point in these previously stabilised subjects was 3.5 points in favour of PP (6.0 vs 2.5; p = 0.025). The rates of TEAEs and AEs of interest appeared similar. CONCLUSIONS: This analysis supports maintenance of effect with the injectable compared with the oral formulation of paliperidone in patients with schizophrenia. The safety profile of PP was similar to that of paliperidone ER. Future studies are needed to confirm these findings.